Thin Layer Chromatographic Analysis of Food Colorants from Three Morphotypes of Annatto (Bixa orellana L.) (International Journal of Agricultural Research, Innovation and Technology, 2013)
This article describes a simple solvent extraction method for the extraction of colorants from the three morphotypes such as, (Morphotype-1 (M1), Morphotype-2 (M2), and Morphotype- 3 (M3) of Annatto (Bixa orellana L.) seeds, and their separation, vivid, and qualitative demonstration by thin-layer chromatography. Several solvent systems (hexane, chloroform, acetone, ethanol, and a mixed-solvent having composition of CHCl3/C2H5OH/CH3COOH (80:2:1)) were applied for extraction of colored components. It was observed that a large portion of colorants was extracted by chloroform. Its effluent was deep brick red in color and transparent. Furthermore, various carrier solvent systems (Benzene-Ethyl acetate) were used to separate the components from the extracts. Carrier solvent system with the ratio of 7:3 was found as superior solvent for chloroform extracts. Three colored-spots were observed for all morphotypes. Among them, the first one was yellow colored having very low polarity and the second and third spots were both redbrick colored having medium and higher polarity respectively. In addition, for M1 no colorless-spot was observed in low and medium polar systems, revealing that the amount of wax and gum were minimum in the extract and superior morphotype among the three. DOI: http://dx.doi.org/10.3329/ijarit.v2i1.13987 Int. J. Agril. Res. Innov. & Tech. 2 (1): 7-12, June, 2012